Metáfora y escenografía: estrategias creativas de abordaje del proyecto escenográfico. - López-Rodríguez, Silvia; Alonso-Calero, José María (South Florida Publishing, 2022)
In this paper we will discuss about the teaching process of the subject “Scenography” in the Faculty of Fine Arts of the University of Malaga. This subject belongs to the area of Sculpture, and it tries to question the process of artistical creation of a scenographic space and provides an active training and keep some proposals that develop the researching and experimental spirit of the students at a formal level as much as conceptual one. The approach in this subject seeks for generating a formative space which motivates the research and creativity of the students and promotes the quest of new expressive and symbolic alternatives in the design and creation of scenographic spaces.
Metaphor and scenography: creative strategies for approaching the scenographic project.
Política de acceso abierto: https://ojs.southfloridapublishing.com/ojs/index.php/jdev/openaccess
Keywords: Escenografía; Investigación activa en educación; Scenography; Teaching; Spatial experimentation; Model